Calcification of the Internal Pudendal Artery and Development of Erectile Dysfunction in Adenine‐Induced Chronic Kidney Disease: A Sentinel of Systemic Vascular Changes. (1st October 2014) - Maio, M. Tina; McCabe, Kristin M.; Pruss, Cynthia M.; Pang, Judith J.; Laverty, Kimberly; Holden, Rachel M.; Adams, Michael A.
Abstract: Introduction: Chronic kidney disease (CKD), erectile dysfunction (ED), and cardiovascular disease share common vascular etiologies and risk factors. Aim: Using a rat model, this is the first study to characterize the consequences of CKD in the onset and development of ED associated with differential regional vascular calcification and circulatory changes. Methods: Stable CKD was generated at 3 weeks in male Sprague‐Dawley rats given dietary adenine and progressed until 7 weeks. Mineral content and morphometry were assessed in the internal pudendal arteries (IPAs), thoracic aorta, and carotid artery. Endothelial function was determined via changes in serum von Willebrand factor (VWF) and endothelium‐dependent relaxation of the thoracic aorta. Results: In severe CKD rats, calcium and phosphate content in all arteries increased, and pulse wave velocity was elevated. Distal IPA segments, in particular, were the first to calcify, but penile tissue per se did not. CKD rats had endothelial dysfunction, as indicated by a decrease in acetylcholine‐mediated relaxation (∼40%) and an increase in serum VWF (∼40%), as well as increased lumen diameter (20%) of the distal IPA. Erectile function, assessed using a centrally acting dopaminergic agent, was significantly impaired by 7 weeks (∼40%). Conclusions: In CKD, the distal IPA appears to be more susceptible to vascular dysfunction and calcification. Additionally, the onset of ED may be an important sentinel of impending systemic vascular disease. To confirm this concept, future experimental and clinical studies will need to examine a range of vessel types and the use of supplementary methods to assess erectile function.